2010
DOI: 10.1161/atvbaha.110.209163
|View full text |Cite
|
Sign up to set email alerts
|

α6-Integrin Subunit Plays a Major Role in the Proangiogenic Properties of Endothelial Progenitor Cells

Abstract: Objective-Alpha6 integrin subunit (␣6) expression is increased by proangiogenic growth factors such as vascular endothelial growth factor (VEGF) and fibroblast growth factor. This increase correlates with enhanced in vitro tube formation by endothelial cells and their progenitors called Endothelial Colony-Forming Cells (ECFCs). We thus studied the role of ␣6 in vasculogenesis induced by human ECFCs, in a mouse model of hindlimb ischemia. Methods and Results-We used small interfering RNA (siRNA) to inhibit ␣6 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 35 publications
4
54
0
Order By: Relevance
“…21 Cord blood-derived ECFCs have previously been reported to enhance neovascularization using in vivo hindlimb ischemia models. 7,[22][23][24] However, the underlying mechanisms have remained elusive to date. Therefore, we set out to selectively eliminate ECFCs 2 weeks after infusion into a hindlimb ischemia model to assess whether selective killing of KDR ϩ ECFCs would lead to disruption of a newly created vascular network and subsequent decline in limb perfusion.…”
Section: E18 Arterioscler Thromb Vasc Biol February 2012mentioning
confidence: 99%
“…21 Cord blood-derived ECFCs have previously been reported to enhance neovascularization using in vivo hindlimb ischemia models. 7,[22][23][24] However, the underlying mechanisms have remained elusive to date. Therefore, we set out to selectively eliminate ECFCs 2 weeks after infusion into a hindlimb ischemia model to assess whether selective killing of KDR ϩ ECFCs would lead to disruption of a newly created vascular network and subsequent decline in limb perfusion.…”
Section: E18 Arterioscler Thromb Vasc Biol February 2012mentioning
confidence: 99%
“…EPC can support neovessel formation in vivo through three different mechanisms [45]: (1) they form new vessels by themselves, (2) they insert into the murine endothelial lining of the murine vasculature, or (3) they exert a paracrine effect. Since we have previously demonstrated in the same model of ischemia that ECFC are integrated into the new murine vessels [46], it is conceivable that preconditioned ECFC exhibit a similar behavior and contribute structurally to this process. Nevertheless, although it has been reported that late outgrowth EPC such as ECFC exert no significant paracrine angiogenic effect [26,45] the possibility that acidosis increases the paracrine action of these cells is being currently studied in our laboratory.…”
Section: Discussionmentioning
confidence: 95%
“…a 6 b 1 is another b 1 -integrin that promotes EPC homing to the sites of ischemia and vascular remodeling and has been shown to be essential for skin homeostasis and regulates endothelial tube formation. 27 It is a laminin-binding integrin and is regulated by factors such as VEGF and bFGF, which are the major growth factors that regulate wound healing. 28,29 EPC adhesion to denuded vessels is also mediated by integrins a v b 3 and a v b 5 .…”
Section: Role Of Integrins In Epc Biology and Functionmentioning
confidence: 99%